Natural convection-radiation from a vertical base-fin array with emissivity determination - Korada, V.S. (EDP Sciences, 2014)
Experiments have been conducted to determine the emissivity for black chrome coated and uncoated aluminum surfaces. The emissivity of the surfaces is estimated considering combined convection radiation heat transfer and observed to be a constant in the range of 60 to 110Â°C. The combined heat transfer coefficients from black chrome coated vertical base vertical fin array of size 70 x 70 mm consisting of 22 aluminum fins with a fin spacing of 10 mm by natural convection and radiation has been determined at different heat inputs. Theoretical analysis of single fin geometry of constant thickness considering both convection and radiation has been used to predict the temperature distribution and heat flow. The theoretical values of heat flow estimated for a fin array is in good agreement with the experimental observations validating the emissivity of the surface. The experimental data is further validated with the equations of Nusselt presented by Churchill and Chu. Â© 2014 Owned by the authors, published by EDP Sciences.